Policy Implementation of Voter List Update in Sidenreng District Rappang - Andi Syaiful; Sulaiman Asang; Muhammad Yunus (Enrichment : Journal of Management, 2021)
The purpose of this study was to determine how the implementation of the voter list updating policy at the General election Commission (KPU) of Sidenreng Rappang Regency so that it can obtain an overview of the extent of the influence of the policy in producing a quality voter list. The theory used is the implementation theory developed by Merilee S. Grindle. which states that policy implementation statements are determined by policy and policy context. Furthermore, it is carried out form each stage of the existing program. The study used a qualitative research with as many as 10 people, namely from the General Election Commission Sidrap commissioner, the General Election Supervisory Agency commissioner Sidrap, officials from the population and Civil Registry Service as well as the community.